2021
DOI: 10.1016/j.fochx.2021.100129
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fecal fermentation characteristics of bamboo shoot (Phyllostachys edulis) polysaccharide

Abstract: Highlights BSP increased production of SCFAs and CO 2 while reduced the ammonia concentrations. BSP fermentation increased the diversity of the bacterial communities. BSP fermented by intestinal microbiota to produce beneficial organic acid metabolites. BSP with potential prebiotic properties were beneficial to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…The butyric acid-producing Firmicutes could improve the gut function by increasing butyric acid concentrations in colon. Whereas the acidic environment promotes the growth of the Firmicutes, it has an inhibitory effect on the acid-sensitive Bacteroidetes, which was consistent with the results we observed from SCFAs. Similar results were obtained in Sparassis crispa polysaccharide and bamboo shoot polysaccharide. , The abundance of the Proteobacteria all increased significantly after fermentation, mainly due to an increase in Escherichia coli.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The butyric acid-producing Firmicutes could improve the gut function by increasing butyric acid concentrations in colon. Whereas the acidic environment promotes the growth of the Firmicutes, it has an inhibitory effect on the acid-sensitive Bacteroidetes, which was consistent with the results we observed from SCFAs. Similar results were obtained in Sparassis crispa polysaccharide and bamboo shoot polysaccharide. , The abundance of the Proteobacteria all increased significantly after fermentation, mainly due to an increase in Escherichia coli.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were obtained in Sparassis crispa polysaccharide and bamboo shoot polysaccharide. 66,67 The abundance of the Proteobacteria all increased significantly after fermentation, mainly due to an increase in Escherichia coli. However, the relative abundance of Proteobacteria in the levan group was lower than in other groups; previous studies have found that a bloom of Proteobacteria in the gut usually implies a dysbiosis of the intestinal microflora, which may lead to diseases such as gastric cancer, liver disease, or inflammatory colitis.…”
Section: Effect Of Levan On Microbial Diversitymentioning
confidence: 99%
“…acid and is now widely recognized for its role in maintaining human health and regulating immune function [39]. However, Enterococcus is by far one of the most important pathogens of hospital-acquired infections and most often causes urinary tract infections.…”
Section: Composition Of Gut Microbiotamentioning
confidence: 99%
“…SCFAs are chemical compounds consisting primarily of acetate, propionate, and butyrate, which possess the ability to not only modulate the makeup of the gut microbiota, but also regulate the host's metabolism [5]. In addition, research has shown that polysaccharides could adjust the structure of the gut microbiota by promoting the proliferation of beneficial bacteria, such as Lactobacillus [6] and Bacteroidetes [7].…”
Section: Introductionmentioning
confidence: 99%